(untitled) (Journal of the College of Basic Education, 2022)
This study carried out to determine the effect of ethanol and aqueous extract of celery on level of sugar and lipid in blood and level of W.B.C ,Hb and P.C.V. In this study using ethanol and aqueous celery extract on five groups of mice that given diet with high level of fat and given glucose ,the first group control without given extract will second and third groups given ethanol extract with concentration (25 , 50 mg/ ml) respectively and forth and fifth groups given aqueous extract with concentration (25 , 50 mg/ ml) respectively and then collected blood from five groups after week and then determent the level of sugar and lipid ( High density level HDL, Low density level LDL ,Tri glycerol lipid TG, Total cholesterol TC) in blood and W.B.C ,Hb and P.C.V. The result suggest decrease the level of sugar and lipid in blood after given extract and notes increase with W.B.C ,Hb and P.C.V. , that result beneficial effect of extract as decrease in level of sugar and lipid in blood also positive effect on constant of blood. Celery ,TC,TG